2011
DOI: 10.1007/s10661-011-2014-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and sources of PAHs using three pine species along the Ebro River

Abstract: Needles of three pine species (Pinus halepensis, Pinus pinea and Pinus nigra) were analysed to assess the occurrence of polycyclic aromatic hydrocarbons (PAHs) in 34 sites located throughout the Ebro River, in Northeast Spain. Overall, the concentration varied between 55 and 808 ng g(-1) (dry weight). The three- and four-ring PAHs were the most representative, with phenanthrene having 43% of the total PAH load and naphthalene showing a high incidence in rural areas. Despite matrix apparent similarities, P. hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…PAHs are present in the atmosphere in vapor and particle-bound phase and can be deposited on soil, water, sediments, and living organism tissues by wet and dry deposition (De Nicola et al 2011). Vegetation is an effective media for catchment of these compounds mainly through atmospheric deposition (Ratola et al 2012). Several taxa have been commonly used as biomonitors, such as mosses, lichens, and tree leaves (Shukla and Upreti 2009; Prajapati and Triphati 2008; Zechmeister et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAHs are present in the atmosphere in vapor and particle-bound phase and can be deposited on soil, water, sediments, and living organism tissues by wet and dry deposition (De Nicola et al 2011). Vegetation is an effective media for catchment of these compounds mainly through atmospheric deposition (Ratola et al 2012). Several taxa have been commonly used as biomonitors, such as mosses, lichens, and tree leaves (Shukla and Upreti 2009; Prajapati and Triphati 2008; Zechmeister et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several taxa have been commonly used as biomonitors, such as mosses, lichens, and tree leaves (Shukla and Upreti 2009; Prajapati and Triphati 2008; Zechmeister et al 2006). Pine needles are considered as an important matrix for the biomonitoring of PAHs because of their relatively long life-span and lipidic waxy cover prone to accumulate airborne contaminants (Ratola et al 2010; 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Indications pertaining to the handling of packaging, that is, whether this should be closed (airtight) Piccardo et al, 2005;Ratola et al, , 2011aRatola et al, , 2012 or be left open Lindroos et al, 2007) could be found in 30% of the publications that specified packaging materials. The materials used in those cases are exclusively plastic or glass.…”
Section: Sample Packaging and Transportmentioning
confidence: 99%
“…The green parts of vegetables or skin of fruits are provided with an epicuticular wax which acts as a sorbent for lipophylic contaminants (Ratola et al, 2011). It is necessary evaluate crops from semi-rural zones of Mexico City by periodically to assess good quality of products of organic contaminants such as aromatic hydrocarbons.…”
Section: Cropsmentioning
confidence: 99%